Coral diseases of mushroom coral (Fungiidae) in Pari Island, Kepulauan Seribu, Jakarta. Issue 1 (December 2021) - Subhan, B; Zamani, N P; Rahmawati, F; Arafat, D; Bramandito, A; Khairudi, D; Santoso, P; Royhan, Q M; Madduppa, H; Rizqydiani, M
Abstract: Coral disease is one of the causes of the decline in the condition of coral reef ecosystems. This study aims to measure coral health based on the abundance and prevalence of coral health categories. The research was conducted in the Pari Island Cluster, Seribu Islands at four stations. The Belt Transect method with 2 × 100 meters was used to calculate coral health and a 30 m Line Intercept Transect (LIT) with three replications to determine substrate cover. The condition of coral reefs can be categorized as moderate to good based on this percentage value. The study results found five genera from the Fungiidae, namely Fungia, Ctenactis, Herpolitha, Heliofungia, and Sandalolitha . The most commonly found genus is the genus Fungia . The health condition of Fungiidae corals in Pari Island is divided into two categories, namely 35% healthy and 65% unhealthy, consisting of changes in tissue color - white (coral bleaching), changes in tissue color - not white (yellow band disease), and compromised health (damage by sedimentation). Yellow band disease is only found in the genus ˆ and is not found in other genera.